Design Feed Forward Neural Network to Determine Doses of the Decongestant for Cold Pills - Tawfiq, L. N. M.; Al-Mayouf, Y. R. B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to design feed forward neural network to determine the effects of cold pills and cascades from simulation the problem to system of first order initial value problem. This problem is typical of the many models of the passage of medication throughout the body. Designer model is an important part of the process by which dosage levels are set. A critical factor is the need to keep the levels of medication high enough to be effective, but not so high that they are dangerous.